Distinct sets of tethering complexes, SNARE complexes, and Rab GTPases mediate membrane fusion at the vacuole in Arabidopsis - Takemoto, Kodai; Askani, Jana Christin; Krüger, Falco; Andrés González, Zaida; Schumacher, Karin (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Membrane trafficking plays pivotal roles in various cellular activities and higher-order functions of eukaryotes and requires tethering factors to mediate contact between transport intermediates and target membranes. Two evolutionarily conserved tethering complexes, homotypic fusion and protein sorting (HOPS) and class C core vacuole/endosome tethering (CORVET), are known to act in endosomal/vacuolar transport in yeast and animals. Both complexes share a core subcomplex consisting of Vps11, Vps18, Vps16, and Vps33, and in addition to this core, HOPS contains Vps39 and Vps41, whereas CORVET contains Vps3 and Vps8. HOPS and CORVET subunits are also conserved in the model plant Arabidopsis. However, vacuolar trafficking in plants occurs through multiple unique transport pathways, and how these conserved tethering complexes mediate endosomal/vacuolar transport in plants has remained elusive. In this study, we investigated the functions of VPS18, VPS3, and VPS39, which are core complex, CORVET-specific, and HOPS-specific subunits, respectively. Impairment of these tethering proteins resulted in embryonic lethality, distinctly altering vacuolar morphology and perturbing transport of a vacuolar membrane protein. CORVET interacted with canonical RAB5 and a plant-specific R-soluble NSF attachment protein receptor (SNARE), VAMP727, which mediates fusion between endosomes and the vacuole, whereas HOPS interacted with RAB7 and another R-SNARE, VAMP713, which likely mediates homotypic vacuolar fusion. These results indicate that CORVET and HOPS act in distinct vacuolar trafficking pathways in plant cells, unlike those of nonplant systems that involve sequential action of these tethering complexes during vacuolar/lysosomal trafficking. These results highlight a unique diversification of vacuolar/lysosomal transport that arose during plant evolution, using evolutionarily conserved tethering components.
Gesehen am 06.05.2019